Roteiros de cinema no Brasil: estruturas e formas na escrita das décadas 1920 e 1930 - Carmo, Victor Vinícius do (2017)
The research proposes to study Brazilian scripts of the decades of 1920 and 1930, through publications in the magazines O fan, A cena muda e Cinearte. The objective is to identify and understand the forms and possible particularities of these texts. The development of the study is based on three axes. In the first one, a theoretical reading of the scripts is performed, focusing on the diversity of looks and considering what the practical manuals say about them. In sequence, we present a historical notion of the screenplays, considering the silent era of cinema and the transition to the spoken cinema. Leaving the North American scene, the moment is taken to deal with specificities of the Brazilian scenario, based on articles written for the magazines O fan, A cena muda e Cinearte. Finally, we study scripts published in these same journals, adopting as a technique the critical analysis of these texts. It was tried to understand what were the characteristics of the Brazilian cinematographic writing of the 1920s and 1930s. In thinking the scripts as historical objects, this research encourages new studies on the subject, observing the scarcity of this discussion in the academic scope. The research also concludes that the Brazilian scripts of this period were directly related to North American writing standards, despite having specific traits and experimentation.